TEACHER IMPROVEMENT THROUGH TRANSFORMATIONAL LEADERSHIP STRENGTHENING, ORGANIZATIONAL CULTURE, EMPOWERMENT, AND PEDAGOGICAL COMPETENCE: Path Analysis and SITOREM Study on Private Vocational School Teachers in Depok - Mailizar Mailizar; Prof. Dr. Sri Setyaningsih; Dr. Taufik (SUJANA: Education and Learning Review, 2024)
The availability of competent productive teachers will have a synergistic impact in achieving quality vocational education. In addition, the position of vocational productive teachers is very strategic in preparing the quality of graduates who can be accepted in the workplace. Unfortunately, in fact, the conditions for the absorption of vocational graduates who have the opportunity to create a workforce that is skilled in their fields are still not optimal. Therefore, this research was conducted to find out and examine the improvement of teacher performance through strengthening transformational leadership, organizational culture, empowerment, and pedagogical competence in private vocational schools in Depok. This research was conducted using a combination method between quantitative research with path analysis techniques and SITOREM analysis. Based on the research results and discussion, the general conclusion of this research is that there are strategies in improving teacher performance, such as strengthening the variables of transformational leadership, organizational culture, empowerment, and pedagogical competence. There are also several strategies that can be used to improve teacher performance by improving the indicators that are still weak in each variable to be improved immediately.